2011
DOI: 10.1139/g11-036
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the H genome in StH-genomic Elymus species based on the single-copy nuclear gene DMC1

Abstract: Previous studies have suggested that the H haplome in Elymus could originate from different diploid Hordeum species, however, which diploid species best represent the parental species remains unanswered. The focus of this study seeks to pinpoint the origin of the H genome in Elymus. Allopolyploid Elymus species that contain the StH genome were analyzed together with diploid Hordeum species and a broad sample of diploid genera in the tribe Triticeae using DMC1 sequences. Both parsimony and maximum likelihood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
9
0
3
Order By: Relevance
“…Origin of H genome in StH -genome Elymus species based on single copy nuclear gene DMC1 has previously been discussed [30]. DMC1 sequence data also showed a reticulate relationship of American polyploid species and diploid Hordeum [35].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Origin of H genome in StH -genome Elymus species based on single copy nuclear gene DMC1 has previously been discussed [30]. DMC1 sequence data also showed a reticulate relationship of American polyploid species and diploid Hordeum [35].…”
Section: Discussionmentioning
confidence: 80%
“…The single copy nuclear gene disrupted meiotic cDNA (DMC1) has been applied to phylogenetic analyses in Triticeae species. The DMC1 sequences used in this study were collected from previously published sources [21], [30][35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…alaskanus, E. caninus, E. hyperarticus, E. violaceus, and E. virescens as well as the presence of a chloroplast minisatellite and suggested that these genetic regions would be excellent candidates for "population structure" analysis. Although Sun and Zhang (2011) found that the H genomes in E. canadensis, E. sibiricus and E. multisetus were highly differentiated from the H genome in Hordeum and other Elymus species, they were not enough to discriminate the species.…”
Section: Classificatory Discriminant Analysis Does Not Identify Speciesmentioning
confidence: 84%
“…Phylogenetic analyses have demonstrated multiple origins of the H and St haplome in the StH tetraploid species of Elymus [1722] and reticulate evolution in the Elymus [17, 18, 2022] . The studies on genetic diversity of E .…”
Section: Introductionmentioning
confidence: 99%